PENGARUH PEMBERIAN ELISITOR EKSTRAK KHAMIR Saccharomyces cerevisiae Hansen TERHADAP KANDUNGAN AJMALISIN DALAM KULTUR AGREGAT SEL Catharanthus roseus (L.) G. Don. - Ratnasari, Jujun; Siregar, Arbayah H; RE, Rizkita (BERITA BIOLOGI, 2001)
There were many ways to obtain high production of secondary metabolites in plant tissue culture; among the other is elicitation.An experiment to study the effect of elicitor derived from Saccharomyces cerevisiae Hansen extract on ajmalicine content in cell aggregates culture of Catharanthus roseus (L.) G.Don, has been conducted. The media used for callus induction and cell aggregates culture were Zenk 6 5(1977) with addition of 2.5 x 10" M Naphthalene Acetic Acid (NAA) and 10 M 6-Benzilaminopurine (BAP).The cell aggregates culturewas subcultured three times and then elicitated with elicitor derived from autoclaved 5.cerevisiae extract at concentrations 0.5, 1.0, 2.5%,and harvested at 18, 24,and 36 hours after elicitation.The ajmalicine was analyzed qualitatively and quantitatively by using High Pressure Liquid Chromatography (HPLC) connected to chromatopack CR-7A Plus. The cell aggregates of C. roseus culture produced ajmalicine both in the cells and the media.The result of elicitation showed that ajmalicine content was influenced significantly by concentration and harvesting time. The highest ajmalicine content in the cell aggregates was 25.288 Â± 0.102 jig/g dw, whilst that in media was 524.600 Â± 0.566 \ML. The optimum concentration of S. cerevisiae extract was 0.5%, and the best harvesting time was 24 hours.